The 2012 Ming K Jeang award for excellence in cell & bioscience - Shi, Yun-Bo (BioMed Central, 2013)
Three research groups led by Dr. Lixin Feng of Shanghai JiaoTong University School of Medicine, Shanghai, China, Dr. Walter Wahli of University of Lausanne, Lausanne, Switzerland, and Dr. Gutian Xiao of University of Pittsburgh Cancer Institute, Pittsburgh, USA, won the 2012 Ming K Jeang Award for Excellence in Cell & Bioscience.